Transforming Sustainable Tourism and Hospitality through Innovative Smart Practices - Kumari, Madhu; Kumar, Suneel; Devi, Nisha; Kumar, Anil (Palash: A Journal of Hospitality and Tourism Service Management, 2025)
Digitization encompasses the transformation of analogue information into a digital format, spanning a broad spectrum of data conversion. The aim of endeavours like Digital India is to harness the power of technology to elevate productivity through the effective use of digitized data and information. By integrating digital tools into business processes, these initiatives seek to optimize efficiency and foster growth within the economy. Since 2014, the government has placed a strong emphasis on digitization. Among the industry’s leading the charge in this regard is the tourism and hospitality sector, which is still seeing rapid growth. This dynamic arena reflects the dynamics of several players in the tourism industry. The tourist sector has embraced digitalization and incorporated it into its operations to provide new travel routes and ways to increase guest satisfaction. It’s a prevalent misconception that digitalization in tourism is restricted to online hotel reservations and electronic payments. UN Secretary General Antonio Guterres emphasizes the pivotal role of tourism in preserving both natural and cultural heritage. However, the expansion of tourism in various regions and countries brings significant impacts on natural resources, consumption patterns, pollution levels, and social dynamics. “Sustainable tourism and hospitality management” aims to achieve a balanced integration of three key facets of tourism development: environmental, economic, and socio-cultural. Consequently, this concept has gained significant traction among travel agencies, emphasizing the importance of fostering harmony among these aspects for long-term viability and positive impact. The objective of this delicate equilibrium is to ensure the enduring sustainability of the tourism sector. In order to be sustainable, we need to consider the social and economic effects of our actions on people as well as the environment. Therefore, the foundational principles of sustainable tourism encompass social equity, environmental preservation, and economic prosperity